2009
DOI: 10.1021/jp902454b
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Photoactive Centers in N-Doped In2O3 Visible Photocatalysts for Water Oxidation

Abstract: N-doped In2O3 films and powders were synthesized, characterized, and evaluated for photoelectrochemical water splitting. The synthetic process was followed in detail by FTIR and UV−vis spectroscopy and the In complex was characterized by X-ray crystallography. NMR, XPS, and EPR were combined in an effort to track the N speciation at each step of the synthesis. The structural, optical and photoelectrochemical properties of the final products (films and powders) were analyzed. Compared to undoped In2O3, N-doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 88 publications
4
64
1
Order By: Relevance
“…Examples include MnWO 4 [14], PbTiO 3 [16], LiFePO 4 [17], In 2 O 3 [13,[18][19][20], PbWO 4 [21], LaPO 4 [5], and so on. In 2 O 3 , an important n-type semiconductor with a direct band gap of 3.55-3.75 eV, has been extensively studied and applied in the field of solar cells [22], transistor [23], photocatalysis [24] and gas sensors for detection of ethanol [13], 2-chlorophenol [20], NO 2 [25], NH 3 [26], H 2 S [27], and CO [28]. Up to now, various wet-chemical routes, such as hydrothermal/solvothermal reaction [29,30], sonohydrolysis [31], nanocasting procedure [32,33], and sol-gel technique [34], have been employed to generate diverse In 2 O 3 nanomaterials with controllable structure and morphology including nanotubes [35], nanocubes [36], nanofibers [37], nanorods [36], hollow spheres [13], and mesoporous In 2 O 3 [32,33,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include MnWO 4 [14], PbTiO 3 [16], LiFePO 4 [17], In 2 O 3 [13,[18][19][20], PbWO 4 [21], LaPO 4 [5], and so on. In 2 O 3 , an important n-type semiconductor with a direct band gap of 3.55-3.75 eV, has been extensively studied and applied in the field of solar cells [22], transistor [23], photocatalysis [24] and gas sensors for detection of ethanol [13], 2-chlorophenol [20], NO 2 [25], NH 3 [26], H 2 S [27], and CO [28]. Up to now, various wet-chemical routes, such as hydrothermal/solvothermal reaction [29,30], sonohydrolysis [31], nanocasting procedure [32,33], and sol-gel technique [34], have been employed to generate diverse In 2 O 3 nanomaterials with controllable structure and morphology including nanotubes [35], nanocubes [36], nanofibers [37], nanorods [36], hollow spheres [13], and mesoporous In 2 O 3 [32,33,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group synthesized N-doped and C-doped In 2 O 3 and showed that In 2 O 3 can be suitably doped with anions to produce a promising photocatalyst with smaller band gap and improved photoelectrochemical properties [16][17][18]. Previous work on N-doped WO 3 shows that nitrogen doping is an effective way to reduce the band gap of WO 3 [19,20], however, the photoelectrochemical performance of N-doped WO 3 films has not been promising.…”
Section: Introductionmentioning
confidence: 99%
“…5,15,[19][20][21][22] Unique to In 2 O 3 facets is that polar {001} facets have the capability to dissociate adsorbed H 2 O molecules into H + and OH − , whereas nonpolar {111} facets cannot do so. 5,15 This suggests that the photocatalytic activity can be enhanced appreciably by precise cutting of the specific crystal facets.…”
mentioning
confidence: 99%